2012
DOI: 10.4172/jcsb.1000092
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition Studies of Naturally Occurring Terpene based Compounds with Cyclin-Dependent Kinase 2 Enzyme

Abstract: The knowledge of the molecular basis of carcinogenesis has helped to discover new, less toxic chemotherapy agents. At present, considerable attention has been focused on identifying the molecular level interactions of naturally occurring Terpene based substances, capable of inhibiting target enzymes. CDKs enzymes are known as cell regulators in eukaryotic cell cycle. In finding new anti-cancer agents, CDKs are used as target enzymes, particular among them are CDK2 enzymes.Computer based Chem-office and Autodoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Some of a few results available indicate that there is an inhibitory effect of terpenes on enzymes, but most of these studies were conducted in the field of medicine: Ganatra and Suchak (2012) showed the inhibitory effect of terpene-based phytochemicals on cyclin-dependent kinase 2. Moreover, Bustanji et al (2010) showed an inhibition of pancreatic lipase by terpenes from Ginkgo biloba.…”
Section: Introductionmentioning
confidence: 97%
“…Some of a few results available indicate that there is an inhibitory effect of terpenes on enzymes, but most of these studies were conducted in the field of medicine: Ganatra and Suchak (2012) showed the inhibitory effect of terpene-based phytochemicals on cyclin-dependent kinase 2. Moreover, Bustanji et al (2010) showed an inhibition of pancreatic lipase by terpenes from Ginkgo biloba.…”
Section: Introductionmentioning
confidence: 97%
“…The probability for van der waals interactions rises due to large surface area of the ligand. The presence of seven methyl groups in the compound 3 increases the surface area of the ligand leading to its strong binding with the receptor 27 . The active site of target proteins of CaMKII was found to contain amino acids residues such as aspartate, valine, leucine, phenyl alanine, alanine, glycine, glutamate, arginine and lysine.…”
Section: Discussionmentioning
confidence: 99%
“…Cyclin dependant kinases are central players and govern various events in cell cycle like the initiation, progression and completion. Inhibition of cyclin dependant kinases is proved as to be more novel strategy for the design and discovery of potent anticancer leads specifically targeting cell cycle [11]. The CDK2-cyclin E complex activity is essential for transition from G1 to S phase [12].…”
Section: Introductionmentioning
confidence: 99%